The Impact of Perceived Teacher Support on Exam Anxiety among Higher Vocational Nursing Students in Fujian Province, China: The Mediating Role of Academic Self-Efficacy - Chen, Lingling; Wang, Hsuan-Po; Yin, Nanfang (Journal of China-ASEAN Studies, 2023)
This study investigates the impact of perceived teacher support and academic self-efficacy on exam anxiety among higher vocational nursing students in Fujian Province, considering various background variables. Grounded in the self-efficacy theory, the research explores the relationships among these three variables and examines the mediating effect of academic selfefficacy. Utilizing a convenience sampling method, a questionnaire survey was conducted on 552 nursing students from four higher vocational colleges in Fujian Province. The findings indicate: (1) Significant gender and grade differences exist in perceived teacher support, exam anxiety, and academic self-efficacy. (2) Perceived teacher support has a significant negative impact on exam anxiety. (3) Perceived teacher support has a significant positive impact on academic self-efficacy. (4) Academic self-efficacy has a significant negative impact on exam anxiety. (5) Academic self-efficacy partially mediates the relationship between perceived teacher support and exam anxiety.